Spatial predictions of suitable environments for palsas and peat plateaus in the Northern Hemisphere for recent and future periods ... - Könönen, Oona Helena; Karjalainen, Olli; Aalto, Juha; Luoto, Miska; Hjort, Jan (Zenodo, 2023)
Here we provide raster files of suitable environments for palsas and peat plateaus in the Northern Hemisphere. These files are results of a scientific study by Könönen et al. (2022, preprint). Files are provided in TIFF-format, and they describe the occurrence probability of the suitable environments for palsas and peat plateaus. Könönen, O. H., Karjalainen, O., Aalto, J., Luoto, M., and Hjort, J.: Environmental spaces for palsas and peat plateaus are disappearing at a circumpolar scale, The Cryosphere Discuss. [preprint], https://doi.org/10.5194/tc-2022-135, in review, 2022. ...